(untitled) (Eurasian Scientific Herald, 2025)
This paper develops a linguocultural account of how culture-specific lexicon and conventionalized expressions generate intercultural conflicts in communication and translation, and how such conflicts can be systematically resolved. Building on contrastive Uzbek-Russian evidence, the study extends the analysis to English to show that conflict of meanings emerges not only from denotational mismatch but, more critically, from connotative polarity shifts, taboo asymmetries, register dissonance, and collocational incompatibilities that misguide recipients and destabilize pragmatic intent.